How Gendered Are Finnish Primary School English Language Textbooks : A Quantitative and Qualitative Study of Two Textbook Series - Kuoksa, Katri (My University, 2019)
In this MA thesis, primary school English language textbooks were studied in order to examine how equally the genders are presented and how stereotypical the contents of the books are. Since every educational establishment in Finland must issue an equality plan, this thesis aims to discover if the striving for gender equality in schools could be detected in the teaching material. As school and literature convey the dominant and prevailing attitudes and beliefs in the society and as they can also influence children’s gender views, it is important to be aware of the contents presented for children through textbooks. The material of the study consists of four English language textbooks from two different textbooks series used in primary school in Finland. A textbook corpus was constructed by using the AntConc software, and the textbooks were examined by combining quantitative and qualitative methods and by utilizing techniques from Corpus Linguistics. The textual aspects examined in the thesis were gendered pronouns and other gender-related words, parental words, the gender distribution of the characters and occupational roles. Critical Discourse Analysis (CDA) was chosen for the theoretical framework due to its suitability to uncover uneven power relations and to study discrimination and inequalities that are mediated, controlled and reproduced through discourses. The quantitative examination discovered an underrepresentation of women and dominance of men in every studied category. Men even dominated the frequencies of parental roles, which contradicts the results of many previous studies. The examination of the gender distribution of the characters revealed the most equal representation of women and men from all the categories that were examined. The qualitative analysis uncovered mostly stereotypical portrayal of parental and occupational roles, even more so for men than for women. However, also some non-stereotypical descriptions of occupational and parental roles were discovered in the corpus. The findings of the study suggest an unequal and stereotypical portrayal of the genders, at least regarding the frequencies. The qualitative findings suggest that some previously gendered textual aspects were acknowledged, for example male parental roles and female characters, but there are still improvements to be made in the future to ensure equal gender representations in primary school English language textbooks.